Prevention and Treatment of Osteoporosis Using Chinese Medicinal Plants: Special Emphasis on Mechanisms of Immune Modulation - Hongyan Zhao; Ning Zhao; Peng Zheng; Xiaohong Xu; Meijie Liu; Dan Luo; Huihui Xu; Dahong Ju (Journal of Immunology Research)
Numerous studies have examined the pathogenesis of osteoporosis. The causes of osteoporosis include endocrine factors, nutritional status, genetic factors, physical factors, and immune factors. Recent osteoimmunology studies demonstrated that the immune system and immune factors play important regulatory roles in the occurrence of osteoporosis, and people should pay more attention to the relationship between immunity and osteoporosis. Immune and bone cells are located in the bone marrow and share numerous regulatory molecules, signaling molecules, and transcription factors. Abnormal activation of the immune system alters the balance between osteoblasts and osteoclasts, which results in an imbalance of bone remodeling and osteoporosis. The incidence of osteoporosis is also increasing with the aging of China’s population, and traditional Chinese medicine has played a vital role in the prevention and treatment of osteoporosis for centuries. Chinese medicinal plants possess unique advantages in the regulation of the immune system and the relationships between osteoporosis and the immune system. In this review, we provide a general overview of Chinese medicinal plants in the prevention and treatment of osteoporosis, focusing on immunological aspects.